Watershed Based Farming Systems as Alternative to Shifting Cultivation in North Eastern Region - Satapathy, K K (Journal of Agricultural Engineering, 2003)
Alternate farming systems to shifting cultivation in north eastern region are being developed for attaining the production and productivity goals ensuring sustainable use of natural resources and high efficiency inputs. Watershed based farming system, appropriate soil conservation measures, mixed land use of agri- horti-silvi- pastoral system, subsidiary source of income through livestock rearing, creation of water harvesting and silt retention structure at lower reaches- these are the important distinguishing features of the suggested agricultural strategy on these hill slopes. Some future strategies for weaning the people away from shifting cultivation and improvement of their socio- economic condition have been discussed.